Analisis Pengaruh Komite Audit dan Komisaris Independen terhadap Perubahan Waktu Penyerahan Laporan Keuangan Perusahaan ke Bursa Efek Jakarta - Ratna Septiyanti (Jurnal Akuntansi dan Bisnis, 2007)
Audit committee and independent board of commissioners are the component of corporate governance that required by Badan Pengawas Pasar Modal (Bapepam) to the listed companies on Jakarta Stock Exchange for improving their corporate governance mechanism. This article examines the influence of audit committee and independent board of commissioners on the time of audited annual report submission to the stock exchange. Hypotheses testing were based on the data of 112 listed companies and done by multiple regression method. The result shows that the size of independent board of commissioners and the audit committee that fit with Bapepam requirements, as expected, have a positive influence on the earlier submission time of audited annual report to the stock exchange. The time of forming of the audit committee, not as expected, have a negative influence on the earlier submission time of audited annual report to the stock exchange. This result indicates that audit committee and independent board of commissioners play a significant role in monitoring financial reporting. Audit committee and independent board of commissioners as the corporate governance mechanisms improve the relevance of financial report information by improving the timeliness of audited annual report submission to the stock exchange.